Zeolitic imidazole framework 8 decorated graphene oxide (ZIF-8/GO) mixed matrix membrane (MMM) for CO2/CH4 separation - Nordin, N.A.H.M. (Penerbit UTM Press, 2017)
Recently, metal-organic framework composited with graphene oxide (MOF/GO) has been explored and has shown superior properties compared to both of the parent materials. Thus, this study aims to utilize zeolitic imidazole framework 8 (ZIF-8), a subclass of MOF, decorated graphene oxide (ZIF-8/GO) as filler in mixed matrix membrane (MMM) for CO2 separation. ZIF-8/GO has been successfully synthesized using aqueous room temperature method. Distortion of ZIF-8 structure after GO incorporate was observed from TEM and decreasing pore properties, while their crystal structure are intact. The role of the composite on gas permeation is also evaluated using pure N2, CH4 and CO2. The presence of ZIF-8/GO into membrane has increase CO2 permeance from 59.03 ± 13.87 GPU to 79.92 ± 18.26 GPU with insignificant changes in the gas pair selectivities even only 0.5wt (total solids) of ZIF-8/GO incorporated. © 2017 Penerbit UTM Press. All rights reserved.